The conjugation strategy affects antibody orientation and targeting properties of nanocarriers. Issue 21 (25th May 2021) - Brückner, Maximilian; Simon, Johanna; Landfester, Katharina; Mailänder, Volker
Abstract : The immobilization of antibodies on the nanocarrier surface is influenced by the choice of an appropriate conjugation strategy. We show that a choosing the carbohydrate side chain on the Fc part of antibodies results in a better targeting ability. Abstract : Antibody-modified drug delivery systems in the nano-range have the ability to overcome current challenges for treating diseases due to their high specificity towards the targeted body region. However, no antibody-bound nanocarrier has been clinically approved to date. This missing clinical approval may be a result of the conjugation strategy that influences the spatial orientation of the attached antibody on the nanocarriers' surface. What is not missing, however, is a diverse selection of antibody to nanocarrier conjugation strategies that determine the success of an antibody functionalized drug delivery system. In this paper, two antibody conjugation strategies were compared by conjugating the surface of cross-linked starch iron oxide nanocarriers with specifically modified CD11c monoclonal antibodies. The antibody nanocarrier conjugates, synthesized either by the chemistry of thiol–maleimide coupling or copper-free click chemistry, were analyzed by flow cytometry to determine their binding affinity towards a murine dendritic cell line (DC2.4). In the cell uptake, different antibody amounts on the nanocarrier could induce a dendritic cell uptake for both conjugation strategies. However, blocking experiments further highlighted the importance of the orientation of the antibody on to the nanocarriers' surface. While the antibodies which were attached via the copper-free click chemistry were oriented, maleimide synthesized conjugates presented their antibodies randomly on the surface. Lastly, to evaluate the in vivo properties of the antibody modified nanocarriers, targeting experiments with mouse plasma were performed, and it was proven that the biomolecular corona does not diminish the targeting efficiency.